Hypoglycemia is common in children with cystic fibrosis and seen predominantly in females - BEREKET, ABDULLAH; HALİLOĞLU, BELMA; KARADAĞ, BÜLENT TANER; DEMİRCİOĞLU, SERAP; GÜRAN, TÜLAY; GÖKDEMİR, YASEMİN (WILEY, 2017)
Objective: To determine the prevalence of hypoglycemia in children and adolescents with cystic fibrosis (CF) in 2-hour oral glucose tolerance test (OGTT) and continuous glucose monitoring (CGM) under free-living conditions. Research Design and Methods: Height, weight, body mass index (BMI), hemoglobin A1c (HbA1c), and Forced expiratory volume (FEV1%) were measured in children with CF (aged 5-18 years). Following OGTT, CGM was installed for 3 days. The total hypoglycemic and hyperglycemic time (%) during 3 days was measured. Subjects were categorized according to hypoglycemic time < 3% (hypo -) and = 3% (hypo +). Each category was further divided according to hyperglycemic time < 3% (hyper -) or = 3% (hyper +). Results: OGTT and CGM were sequentially performed in 45 CF patients. The frequency of hypoglycemia in OGTT and hypoglycemic time >= 3% of CGM were 13.3% and 27.5%, respectively. After 5 cystic fibrosis-related diabetes (CFRD) subjects were excluded, the number of subjects in each subgroup was 17 (hypo-/hyper-), 12 (hypo-/hyper+), 6 (hypo+/hyper-), and 5 (hypo+/hyper+). Significantly higher insulin at 120 minutes was observed in OGTT in (hypo +/hyper-), as compared with subgroup (hypo-/hyper-) (P = .018). Total insulin levels were also significantly higher in (hypo+/hyper-), than (hypo-/hyper-), but were similar to those in the healthy control group (P = .049 and P =.076, respectively). There was a female predominance in hypoglycemic subjects both in OGTT and subgroup (hypo+/hyper-) in the CGM group (P = .033 and P = .033, respectively). FEV1 was significantly lower in hypo + group as a whole, and (hypo+/hyper+) subgroup than in (hypo-/hyper-), (P = .044 and P = .042, respectively); the difference was independent of body mass index-standard deviation score (BMI-SDS) (P = .15 and P = .12, respectively). Conclusion: The frequency of hypoglycemia in children with CF was higher in CGM than that in OGTT. Insulin secretion was delayed and total insulin levels increased in the hypoglycemic patients. Glucose instability/hypoglycemia is associated with poorer lung function in patients with CF, independent of nutritional status.
Keywords: cystic fibrosis; hypoglycemia; OGTT; CGM; FEV1; SEX; AGE